Impacto de la inversión extranjera directa sobre la tasa de desempleo en Colombia periodo 2010 - 2020 (2023)
Colombia presents a persistent and high Unemployment Rate (TD) for which this document tries to explain this phenomenon from the point of view of the capacity of Foreign Direct Investment (FDI) to generate jobs; in this case, considering as a hypothesis that there is an inverse relationship between these variables and that the effects of FDI are significant on TD. The first two chapters will address the evolution of these variables in order to analyze their respective behaviors and identify those institutional aspects and shocks that can bias the measurements made in the next chapter, it is found that the DT is maintained despite the different reforms aimed at to labor flexibility, while FDI is sensitive to expectations and is strongly boosted thanks to a legal framework that favors trade.